A distributed modelling method of the transmission tower and transient response analysis of lightning wave process. Issue 21 (25th June 2021) - Huang, Lin; Zhou, Lijun; Wu, Tongshuai; Hu, Chen; Zhang, Dong; Wang, Dongyang; Chen, Sixiang
Abstract: Lightning transient response analysis is the key to determining the lightning resistance level of transmission lines and the performance of lightning protection measures. This paper proposes a distributed modelling method for a typical 110 kV transmission tower and further analyses the lightning transient response. The refined modelling of the nominal height part of the tower is carried out. Then the influence of the refined modelling on the refraction and reflection process of the lightning wave propagation is investigated. Based on the distributed tower model, the impact of the foot distance and the equivalent radius of the main body cylinder on the top overvoltage is studied. Field experiments indicate that the proposed distributed tower model can effectively reflect the transient lightning wave process. Moreover, it can provide technical support for the lightning resistance level of transmission lines and the lightning protection of narrow base towers.